Similar outcome of femoral neck fractures treated with Pinloc or Hansson Pins: 1-year data from a multicenter randomized clinical study on 439 patients. (2nd November 2019) - Kalland, Kristine; Åberg, Henrik; Berggren, Anna; Ullman, Michael; Snellman, Greta; Jonsson, Kenneth B; Johansson, Torsten
Abstract : Background and purpose — There are few reports on the efficiency of the Hansson Pinloc System (Pinloc) for fixation of femoral neck fractures. We compare Pinloc with the commonly used Hansson Pin System in a randomized clinical trial. The primary outcome measure is non-union or avascular necrosis within 2 years. We now report fracture failures and reoperations within the first year. Patients and methods — Between May 2014 and February 2017, 439 patients were included in the study. They were above 50 years of age and treated for a femoral neck fracture at 9 orthopedic departments in Sweden. They were randomized to either Pinloc or Hansson pins. The fractures were grouped as (a) non-displaced regardless of age, (b) displaced in patients < 70 years, or (c) ≥ 70 years old, but deemed unfit to undergo arthroplasty. Follow-up with radiographs and outpatient visits were at 3 and 12 months. Failure was defined as early displacement/non-union, symptomatic segmental collapse, or deep infection. Results — 1-year mortality was 11%. Of the 325 undisplaced fractures, 12% (21/169) Pinloc and 13% (20/156) Hansson pin patients had a failure during the first year. The reoperation frequencies were 10% (16/169) and 8% (13/156) respectively. For the 75 patients 50–69 years old with displaced fractures, 11/39 failures occurred in the Pinloc group and 11/36 in the Hansson group, and 8/39 versus 9/36 patients were reoperated. Among those 39 patients ≥ 70 years old, 7/21 failures occurred in the Pinloc group and 4/18 in the Hansson group. Reoperation frequencies were 4/21 for Pinloc and 3/18 for the Hansson pin patients. No statistically significant differences were found in any of the outcomes between the Pinloc and Hansson groups. Interpretation — We found no advantages with Pinloc regarding failure or reoperation frequencies in this 1-year follow-up. Trial registration: ClinicalTrials.gov identifier: NCT02776631.